Świat badacza i badanego w warunkach zmiany = The world of the researcher and the researched person under conditions of change - Jurewicz, Monika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main aim of the article is to provide theoretical insight into the speci?c meeting between the researcher and the researched person in studies using thebiographical method. This issueseems tobeall the moreimportant because the use of this method imposes a special character of data collection and interpretation. But above all, it determines the speci?c character of relations that take place between the direct participants of this process, i.e. the researcher and the researched person.
Keywords: metoda biogra?czna; relacje pomiędzy badaczem a badanym; zmiana; re?eksja Cli?orda Geertza; biographical method; relations between the researcher and researched person; change; re?ection of Cli?ord Geertz